TINJAUAN LITERATUR: PERAN KOMUNITAS OLAHRAGA DI ERA MODERN DALAM MEMBANGUN SOLIDARITAS SOSIAL - Fander Johannes Pinem; Geubrina Rahman, M.; Pratama Simatupang, Roby; Fasuri Bahri, Farandy; Indra Siregar, Yan; Arima, Putra; Padrevio Pakpahan, Kelvin; Cisse P. Hutabarat, Jibril; Faiz Chaikal Ponto, Mhd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of sports communities in the modern era in building social solidarity within society. The development of sports communities in modern times functions not only as a medium for physical activities but also as a means of social interaction, group identity formation, and strengthening relationships among individuals. The method used in this research is a literature review by collecting various scientific sources such as journals, books, and articles related to the sociology of sport and social solidarity. The results of the study indicate that sports communities have an important contribution in creating togetherness, cooperation, tolerance, and social awareness among members. In addition, the development of social media has expanded sports community networks, thereby strengthening social interaction in the modern era. Therefore, sports communities can serve as an effective medium for building social solidarity amid changes in modern society’s lifestyle.